Development of an information system for blood bag screening as an important step in blood transfusion handling in Indonesia - Abimanyu, Andiani (Eastern-European Journal of Enterprise Technologies, 2025)
The implementation of blood bag screening test is very important to identify and prevent transfusion-transmitted diseases such as hepatitis B, hepatitis C, HIV, and syphilis. This paper discusses the development of a blood bag data filtering information system in Indonesia. The object of this research is the management of blood donor and blood bag data. The results of this study indicate a better operational framework, accurate data management and timely decision-making, related to the safety of blood services. By using modern programming languages such as PHP with the Laravel framework and leveraging the MySQL database, this system integrates blood donor management and screening test results, significantly reducing the risk of disease transmission. The main feature of this system is its ability to effectively integrate donor data and screening results, which allows real-time access and decision-making. This feature enables the system to solve problems previously identified by conventional methods, significantly reducing the risk of errors and disease transmission. The results of the study indicate that the system can be implemented effectively in the internal environment of blood transfusion units in Indonesia, thereby improving operational services and comprehensive reporting. Hence, proper data and information management will result in better decision-making in the health sector, especially in maintaining high blood safety standards. Thus, this study highlights that the developed information system plays an important and effective role in strengthening blood transfusion management in Indonesia, opening up opportunities for continuous training of health workers